Guidelines for Strengthening Communities to Prevent Drug Problems: Guidelines for Strengthening Communities to Prevent Drug Problems - Sombutkhum, Suriyo; Kenaphoom, Sanya (RATANABUTH JOURNAL, 2025)
The drug problem poses a threat to society, the economy, and the quality of life of citizens. Sustainable solutions require building strong communities, emphasizing participation from all sectors. Key approaches include raising awareness through accurate information and preventative activities, instilling positive values, promoting community participation, developing the economy and careers to address economic issues, strengthening family and youth relationships, and integrating cooperation from government, private, and community agencies. Furthermore, drug addiction treatment and rehabilitation are a crucial step in providing them with the opportunity to reintegrate into society with dignity. These integrated actions will help build sustainable community resilience against drug problems in the long term.